DAKWAH MELALUI TEKNOLOGI VR DAN AR: TRANSFORMASI MEDIA DALAM MENYAMPAIKAN PESAN ISLAM - Rahimah (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2024)
Technological advances have penetrated all of society's lives. Almost every corner and human activity is now accompanied by technology, including religious values. Da'wah, which was previously carried out verbally and held in a private house, has now shifted into a space that is not limited by time. For example, the use of Virtual Reality (VR) and Augmented Reality (AR) technology has been carried out in the medical, military, education, robotics and urban planning and civil science fields. Apart from that, the potential use of Virtual Reality (VR) and Augmented Reality (AR) technology can be used as a da'wah media. So the aim of this research is to analyze the potential of using Virtual Reality (VR) and Augmented Reality (AR) in the world of modern preaching. The approach used uses a literature review. The first formulation of the problem is, what is the potential of using Virtual Reality (VR) and Augmented Reality (AR) in the world of modern da'wah? Second, what are the models of Virtual Reality (VR) and Augmented Reality (AR) in the world of modern preaching? The results obtained in this research are that in developing Islamic da'wah, Augmented Reality (AR) technology can be combined with several forms such as: game cards, Islamic propagation story books, brochures/leaflets/poters, and Islamic history museums. Keywords: Da'wah, Media Transformation, Augmented Reality (AR).